1993
DOI: 10.1111/j.1365-2109.1993.tb00552.x
|View full text |Cite
|
Sign up to set email alerts
|

Mortality of marine cultured rainbow trout, Oncorhynchus my kiss (Walbaum), during the summer in the Netherlands

Abstract: Abstract. In northern Europe, rearing of rainbow trout, Oncorhynchus mykiss (Walbaum), in sea cages is a substantial part of fish culture. One of the major constraints for the development of this system in other parts of Europe is the unexplained mortality of fish during the summer. To investigate environmental aspects of this mortality, rainbow trout, cultured in cages in sea water, were monitored from May to October for three successive years. No evidence of bacterial involvement could be found, while water … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0
1

Year Published

1997
1997
2014
2014

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 18 publications
0
2
0
1
Order By: Relevance
“…Fish cultured in saline environment need more energy for maintenance, as shown by Oorschot & Boon (1993) for rainbow trout. Oncorhynchus mykiss (Walbaum).…”
Section: Introductionmentioning
confidence: 99%
“…Fish cultured in saline environment need more energy for maintenance, as shown by Oorschot & Boon (1993) for rainbow trout. Oncorhynchus mykiss (Walbaum).…”
Section: Introductionmentioning
confidence: 99%
“…해수에서 사육된 무지개송어는 담수에서 보다 성 장이 2-3배 빠르며 육질이 우수하기 때문에 상품 성을 향상시킬 수 있는 장점을 가지고 있다 (Austreng et al, 1987;Güner et al, 2006 (Mccarthy et al, 1974;Gastric and Kinkelin, 1980;Oorschot and Boon, 1993;Nolan et al, 2000;Tanrikul, 2007 (Fig. 1a), 해부 결과 비장 비대, 유문수 부위 및 복강근육의 출혈과 위속에 액성물질 및 기포가 가득 차 있었다 (Fig.…”
unclassified
“…Salinity changes can cause stress to the fish due to interference with physiological homeostasis and routine biological processes (Kültz, 2015). Freshwater fish such as red tilapia (Oreochromis mossambicus x O.niloticus) (Hepher et al, 1983), rainbow trout (Oncorhynchus mykiss) (Oorschot and Boon, 1993) need more energy for osmoregulation maintenance when cultured in a saline environment. Nile tilapia, exposed to saline water showed changes in blood parameters (Verdegem et al, 1997), immune function parameters (Choi, 2004), and histopathology (Hassan et al, 2013, de Azevedo et al, 2015, which is suggested to make them more susceptible for infectious disease.…”
Section: Introductionmentioning
confidence: 99%